HUBUNGAN POLA ASUH IBU DENGAN STATUS GIZI BALITA DI POSYANDU JINTEN 11 KELURAHAN BUMIJO DI WILAYAH KERJA PUSKESMAS JETIS - winda dwi puspita; Andi Syarifah Irmadani; Andi Arlina (Jurnal Berita Kesehatan, 2022)
The prevalence of nutritional status based on weight-for-height (W/H) in Yogyakarta indicate that the prevalence of nutritional status of under-five children is very thin (2.6%) and thin (6.5%) (Ministry of Health, 2012). The role of mother as a caregiver and educator for the child in the family may affect the growth and development of the child. In the course of time, the child needs basic necessities such as food, health care, protection, housing and affection. Results of a preliminary study at Posyandu Jinten 11 indicated the prevalence of nutritional status of under-five children with overnutrition (7.58%), well-nourished (65.15%) and undernutrition (27.27%) and all mothers took care of their under-five children fully without working outside the home. This research is a descriptive analytical research with cross sectional approach. The population was all children aged 1-5 years. Sampling employed purposive sampling with a sample size of 57 respondents. Data were collected using questionnaires and Health Cards (KMS). Data were analyzed using Chi Square. Most respondents were elementary education graduates (45.6%), mostly under-five children were 48-59 months (45.6%), and most under-five children were male (66.7%). Parenting style was mostly poor (59.6%), while nutritional status was mostly good (87.7%). There was no correlation between mother’s parenting and nutritional status of under-five children, with p value of 0.197> 0.05. There is no correlation between mother’s parenting and nutritional status of under-five children at Posyandu Jinten 11 Bumijo Village in the Working Area of Puskesmas Jetis.